Search for excited electrons in pp̄ collisions at s=1.96TeV - Abazov, V. M. (2008)
We present the results of a search for the production of an excited state of the electron, e*, in proton-antiproton collisions at s=1.96TeV. The data were collected with the D0 experiment at the Fermilab Tevatron Collider and correspond to an integrated luminosity of approximately 1fb-1. We search for e* in the process pp̄→e*e, with the e* subsequently decaying to an electron plus photon. No excess above the standard model background is observed. Interpreting our data in the context of a model that describes e* production by four-fermion contact interactions and e* decay via electroweak processes, we set 95% C.L. upper limits on the production cross section ranging from 8.9 to 27 fb, depending on the mass of the excited electron. Choosing the scale for contact interactions to be Λ=1TeV, excited electron masses below 756 GeV are excluded at the 95% C.L. © 2008 The American Physical Society.